Comparative study of hypertonic saline nasal douching versus normal saline nasal douching in post operative endoscopic sinus surgery patients - Tripathy, Smruti Milan; Panda, Rakhee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Nasal douching is routinely done in the post operative functional endoscopic sinus surgery (FESS) patients. Douching helps to clear the nasal cavity of crusts, clots and any infected debris and also promotes quicker mucosal healing. Methods: A total of 60 patients who underwent FESS in the ENT department were selected for the study. Patients were randomly allocated into two groups. Group 1 patients were subjected to nasal douching using hypertonic saline (3%) in the post operative period while the group 2 patients used isotonic saline (0.9%) for nasal douching. Patients were followed up on the 7th, 15th and 30th post operative day and various parameters were compared using nasal endoscopy, saccharine clearance test, sinonasal outcome test questionnaire (SNOT-22) and visual analogue scale (VAS). Results: Group 1 patients who used hypertonic saline for nasal douching had a better symptom score on 30th post operative day in SNOT-22 and VAS (p<0.05 in both) as compared with the group 2 patients who used isotonic saline for nasal douching. More patients in group 1 had a healthy and normal appearance of nasal mucosa on endoscopic examination as compared with group 2. There was not much significant difference in the mucocilliary clearance test (MCT) scores of both the group patients. Conclusions: Patients who used hypertonic saline for douching in the post operative period were found to have lesser crusting, nasal obstruction as compared to those who used isotonic saline for douching.